1992
DOI: 10.1007/bf02356958
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibodies to bovine viral diarrhoea virus in Namibian wildlife

Abstract: Pestivirus infection in domestic ruminants has been reported in several parts of southern Africa (Theodoridis and Boshoff, 1974). In'wildlife naturally occurring bovine viral diarrhoea virus (BVDV) infection has only rarely been reported (Plowright, 1969). It was the purpose of this investigation to record the antibody levels to BVDV in 535 sera from the following 9 Namibian wildlife species: roan antelope The sera originated either from wildlife cropping operations in southern Namibia or from the Etosha Natio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

1995
1995
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 2 publications
1
6
0
Order By: Relevance
“…Infection of wild ruminants can result in either acute disease or a subclinical infection (Van Campen et al, 2001). A high prevalence of antibodies against the NADL strain has been recorded in three other related species of Hippotraginae: gemsbok and sable and roan antelope (Hamblin and Hedger, 1979;Soine et al, 1992). Ours is the first study to demonstrate exposure of Arabian oryx to BVDV.…”
Section: Discussionmentioning
confidence: 63%
“…Infection of wild ruminants can result in either acute disease or a subclinical infection (Van Campen et al, 2001). A high prevalence of antibodies against the NADL strain has been recorded in three other related species of Hippotraginae: gemsbok and sable and roan antelope (Hamblin and Hedger, 1979;Soine et al, 1992). Ours is the first study to demonstrate exposure of Arabian oryx to BVDV.…”
Section: Discussionmentioning
confidence: 63%
“…Their identification and removal is considered key to control efforts [5]. Several studies have demonstrated significant seroprevalence in African wildlife, although the role of sheep and wildlife in BVDV transmission is yet to be fully elucidated[6][8]. Once a PI animal enters a herd, it has been assumed that the herd is likely to remain infected due to the ongoing production of PI animals as naïve cows are infected during pregnancy, however, recent evidence suggests that herds may self-clear [9].…”
Section: Introductionmentioning
confidence: 99%
“…Atang and Plowright (1969) reported the isolation of BVD virus from a captive giraffe (Giraffa camelopardalis) in Kenya and also cited the isolation of BVD from a sick buffalo (Syncerus caffer) shot in the Central African Republic, which was apparently involved in an outbreak of disease that affected warthog (Phacocoerus aethiopicus) and eland (Taurotragus oryx). Antibody against BVD virus has been shown to be widespread in domestic and wild species throughout Africa (Hamblin and Hedger, 1979;Nettleton, 1990), although the prevalence of antibody appears to vary for different countries, particularly for wildlife species (Hamblin and Hedger, 1979;Soine et al, 1992). In cattle, a high prevalence of antibody often correlates with the presence of persistently infected animals within the herd and spread is most successfully achieved by close contact with these persistently infected animals (Roeder and Drew, 1984).…”
Section: Discussionmentioning
confidence: 99%